Flotation of Sulphide Minerals Using Organosolv Lignin as Collector—Pilot-Scale Trials - Panagiotis M. Angelopoulos; Georgios Anastassakis; Nikolaos Kountouris; Maria Taxiarchou; Effrosyni Koutsotheodorou; Tilemachos Pefkos; Vasileios Klepkos; Christina Samara; Giorgos Mprokos (Materials Proceedings)
The use of toxic chemicals as flotation reagents raises concerns about the sustainability of the process and its environmental impact. Xanthates are a family of efficient collectors that find application in the selective recovery of lead, gold and zinc ores, but they are toxic, with the majority of them being imported from eastern countries. Recently, organosolv lignin (OLN) micro- and nanoparticles have been produced and tested as collectors in the flotation of Cu minerals with positive results. The material is attractive because it is natural, biodegradable, and possesses a low carbon footprint compared to the conventional reagents. A mixed sulphide ore deposit in Halkidiki, Greece, is operated by Hellas Gold S.A., a subsidiary of Eldorado Gold. The company produces galena (PbS), sphalerite (ZnS) and Au bearing pyrite/arsenopyrite (FeS2/FeAsS) concentrates by applying consecutive froth flotation stages. Our previous laboratory studies have shown that the partial substitution of sodium isopropyl xanthate (SIPX) with OLN is possible, without worsening the flotation performance or downgrading the concentrates’ quality. This study presents the findings of 3-stage pilot-scale flotation tests using OLN as a partial substituent of the SIPX collector on sphalerite and pyrite/arsenopyrite circuits. In the sphalerite recovery circuit, the partial replacement of SIPX with OLN (25 and 50%) resulted in an increase in Zn grade and a similar recovery compared to the standard case, while better selectivity was achieved since the Au recovery in the Zn concentrate was lower. Similarly, with the pyrite/arsenopyrite flotation circuit, the replacement of SIPX with OLN resulted in an increase in gold recovery with a parallel reduction in Pb recovery. It appears that OLN can efficiently replace part of the SIPX collector in Zn and Au flotation, producing concentrates of similar to better purity, in terms of grade and recovery of valuable metals, because of the improved selectivity of the mixed collector. The introduction of OLN in the collector mixture and the parallel reduction of SIPX drastically reduce the environmental footprint of the process.